Immediate effects of trunk stabilizer muscles training on muscle response time in individuals with non-specific chronic low back pain - Poramet Earde (2018)
© 2014, Medical Association of Thailand. All rights reserved. Objective: To investigate immediate effects of biofeedback training on motor control performance in participants with nonspecific chronic low back pain. Material and Method: RCT was conducted. The training group received isolated and co-contraction training of trunk stabilizers in lying on the left side, sitting on stool and sitting on a gymnastic ball, while the control group was asked to rest comfortably on a chair. Trunk muscles response time during rapid arm movement test was recorded using surface electromyography. Two-way ANOVA and Bonferroni post hoc test were used to detect changes within and between groups. Results: In the training group, the trunk muscles response times were significantly decreased after training when compared with those in the control group (p<0.05). Conclusion: Trunk stabilizer training has a beneficial effect on motor response time of the trunk muscles. The long-term effects of exercise should be further considered with a larger sample size.